2009
DOI: 10.4161/cc.8.21.9970
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Kinesin-14 mitotic mechanisms in spindle bipolarity

Abstract: Kinesin-like proteins are integral to formation and function of a conserved mitotic spindle apparatus that directs chromosome segregation and precedes cell division. Ubiquitous to the mechanism of spindle assembly and stability are balanced Kinesin-5 promoting and Kinesin-14 opposing forces. Distinct Kinesin-14 roles in bipolarity in eukaryotes have not been shown, but are suggested by gamma-tubulin-based pole interactions that affect establishment and by microtubule cross-linking and sliding that maintain bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…Mouse KIFC1 has tail domain sequences that target it to membrane-bound organelles (Zhang and Sperry, 2004); the tail domain of Pkl1 direct it to γ-tubulin (Olmsted et al, 2013(Olmsted et al, , 2014. Additional studies in which chimeric kinesin-14 proteins of human HSET, Drosophila Ncd and fission yeast Pkl1 were generated also support this paradigm and confirm that tail domain sequences orchestrate function (Simeonov et al, 2009). …”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…Mouse KIFC1 has tail domain sequences that target it to membrane-bound organelles (Zhang and Sperry, 2004); the tail domain of Pkl1 direct it to γ-tubulin (Olmsted et al, 2013(Olmsted et al, , 2014. Additional studies in which chimeric kinesin-14 proteins of human HSET, Drosophila Ncd and fission yeast Pkl1 were generated also support this paradigm and confirm that tail domain sequences orchestrate function (Simeonov et al, 2009). …”
Section: Introductionmentioning
confidence: 59%
“…The function of spindle pole organization and microtubule nucleation does not need to be distinct, and some kinesin-14 members, such as HSET, might possess both capabilities of spindle pole organization and microtubule nucleation (Walczak et al, 1997;Simeonov et al, 2009). It is worth noting that in meiotic cells and in somatic cells, spindles can nucleate around chromosomes in the presence of a Ran gradient and this may explain in part the evolutionary need for kinesin-14 members to have dual roles with γ-tubulin complexes at the different Ran-GTP concentrations (Khodjakov et al, 2000;Khodjakov and Rieder, 2001).…”
Section: Interactions Of Mtoc Proteins and Microtubule Minus-endsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, we observed that anaphase cells in logarithmically growing cultures lacking CaKar3 and CaCik1 have spindles that are indistinguishable from those of the wild type in static images and that these do not collapse during anaphase. The S. pombe kinesin-14 counterpart to ScKar3/Vik1, named Pkl1, also displays SPB localization (91), and a recent study suggested that S. pombe Pkl1 and the kinesin-5 homolog Cut7 antagonistically regulate microtubule nucleation from the ␥-TuRC complex (92). This is intriguing because GFP-labeled C. albicans Kip1 (kinesin-5) also localizes prominently to the SPB, with a smaller quantity localizing with the spindle itself (10).…”
Section: Discussionmentioning
confidence: 92%